2008
DOI: 10.2223/jped.1752
|View full text |Cite
|
Sign up to set email alerts
|

Toilet training: methods, parental expectations and associated dysfunctions

Abstract: ResumoObjetivo: Revisar a literatura científica e leiga sobre o treinamento esfincteriano, abordando expectativas dos pais, métodos disponíveis para aquisição do controle esfincteriano e morbidades associadas. Fontes dos dados: Síntese dos dados:Os pais apresentam expectativas irreais sobre idade de retirada de fraldas, sem levar em conta o desenvolvimento infantil. As estratégias de treinamento não se modificaram nas últimas décadas, e a idade vem sendo postergada na maioria dos países. Métodos de treinament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0
20

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 74 publications
5
66
0
20
Order By: Relevance
“…Koff et al reported that dysfunctional elimination syndromes are associated with late reflux disappearing and an increase in urinary infection (14). Mota et al highlighted that wrong training may be a causative factor for bladder and intestinal disorders (17). Fonseca et al pointed out a high prevalence of lower urinary tract symptoms in children with nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…Koff et al reported that dysfunctional elimination syndromes are associated with late reflux disappearing and an increase in urinary infection (14). Mota et al highlighted that wrong training may be a causative factor for bladder and intestinal disorders (17). Fonseca et al pointed out a high prevalence of lower urinary tract symptoms in children with nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…We consider this to have been an appropriate sample since 97% of the interviewees were the children's mothers; all of the interviews were conducted by the same interviewer; the majority of the mothers were less than 30 years old and had one or two children; the majority had graduated from primary education; and 90% were married or in a stable relationship. It was observed that 92% of the mothers gained experience with no specialist help, only 7% of them had been given information by a pediatrician and just 3% of informants had acquired toilet training information from the press; all of which indicates very little of the advance guidance that is recommended (13,22,24) .…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Despite this, over recent years toilet training has been being delayed in the majority of countries, with a gradual increase in the age at which control is attained. 9 Healthy bladder and bowel movement habits are important for the healthy function of the systems involved (urinary and intestinal). 9,10 Late acquisition of bladder and bowel control may be related to the increased prevalence of dysfunctional elimination observed over recent years.…”
Section: Introductionmentioning
confidence: 99%
“…9 Healthy bladder and bowel movement habits are important for the healthy function of the systems involved (urinary and intestinal). 9,10 Late acquisition of bladder and bowel control may be related to the increased prevalence of dysfunctional elimination observed over recent years. 9 Other pathologies that may be related to incorrect toilet training are recurrent urinary infections, enuresis, constipation, toileting refusal and encopresis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation